2017 32nd IEEE/ACM International Conference on Automated Software Engineering (ASE) 2017
DOI: 10.1109/ase.2017.8115668
|View full text |Cite
|
Sign up to set email alerts
|

Why and how JavaScript developers use linters

Abstract: A linter is a type of static analysis tool that warns software developers about possible errors in code or violations to coding standards. By using such a tool, errors can be surfaced early in the development process when they are cheaper to fix, and code can be kept more readable and maintainable. For such a tool to be successful, it is important for its creators to understand the needs and challenges of developers when using a linter. Furthermore, it needs to be made clear to developers why using such a tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 64 publications
(154 reference statements)
3
17
0
Order By: Relevance
“…. In our ASE paper[20], we affirmed that these results only contradicted previous literature. In this paper, in the light of new data, we observe that false positives are still an open question in JavaScript linters.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…. In our ASE paper[20], we affirmed that these results only contradicted previous literature. In this paper, in the light of new data, we observe that false positives are still an open question in JavaScript linters.…”
supporting
confidence: 61%
“…This paper extends our previous work "Why and How JavaScript Developers Use Linters" that appeared at the 32nd IEEE/ACM International Conference on Automated Software Engineering (ASE), 2017 [20]. Our previous work included a qualitative analysis of interviews with JavaScript developers, which is now extended with an extensive analysis of linter configurations in OSS projects, along with a survey distributed in the JavaScript community.…”
Section: Introductionmentioning
confidence: 79%
“…After 10 interviews, we noticed a convergence of the collected data and thoughts [40], even considering the difference of technologies mastered by our participants and the types of projects they usually work on. Moreover, 10 is a decent number of participants that is close to the studied population by other similar works [6,13,36,38].…”
supporting
confidence: 72%
“…Current solutions: Taking into consideration the domain and the architecture of the system under study has been gaining attention from the community in the last years. Although linters are widely used [35], [36], and quality monitoring strategies such as Continuous Inspection have been proposed [26], researchers have shown that the domain of the application matters when it comes to the presence of code smells [22], that code metric distributions are statistically different among the different architectural roles of classes in a system [3], [23], and that specific architectures may have their own specific smells [2], [19].…”
Section: Contextually Measuring the Quality Of Object-oriented Somentioning
confidence: 99%